(untitled) (Environmental Smoke, 2024)
Currently, the efforts of marine research and marine resources exploitation are rising. However, debate usually is divided into economic and conservation approaches. One procedure used in Brazil to achieve coherence between economic development and environmental management in exploitation of natural resources is the environmental licensing. In Brazil, this activity is relatively recent and so little is known about the actual negative environmental impacts. The goal of this paper was to evaluate the main positive and negative aspects from environmental licensing process of exploitation of marine algae in Brazil guided by the IBAMA, focusing on processes with operation license emitted or expired. This qualitative research and methodology was developed into different stages between 2014 to 2015, analysis of legislation, information in licensing online systems and consultation in the technical collection of IBAMA head office, in Brasília. From processes evaluated, some of the main negative aspects found were incomplete studies, occurrence of irregularities, time elapsed and judicial intervention. On the other hand, positive aspects were strategies to give more speed and efficiency to processes. For breaching the conditions of operating licenses, all these licenses were suspended. The improvement of environmental licensing is needed and very required by several actors. However, it needs a broad discussion that considers the institutional existing experiences and limitations, mainly under challenges and pressure in its operational, budgetary or political performance.